Let boys explain the world to girls who do not know - visual representations of gender and diversity in Austrian primary textbooks and implications for diversity-sensitive education. Issue 3 (2nd October 2021) - Alter, Grit; Köffler, Nadja
Abstract: Let boys explain the world to girls who do not know - Visual representations of gender and diversity in Austrian primary textbooks and implications for diversity-sensitive education Textbooks do not only offer information on specific topics and delineate competence development but provide insights into a society's socio-cultural norms and values by means of representations . In particular, this refers to the diversity with which classrooms, groups of friends and families are depicted in textbooks. The contribution at hand presents a critical analysis of current Austrian textbooks for the subjects German, Science, Maths and English as a Foreign Language used in primary education. Our analysis reveals a strong tendency towards the depiction of able, white and male protagonists as the norm, presenting an ideology of power from which they explain the world. Female characters are mainly reduced to the activities of wondering, listening to their male counterparts and following their lead. While there are few exceptions, further identities such as Black, Indigenous and People of Colour (BIPoC) or people with physical and/or mental varieties can hardly be found. Applying a qualitative and quantitative content analysis, this study not only considered a numerical diversity in terms of gender, BIPoC and physical and/or mental variety but also investigated the agency of respective characters. Thus, disempowerment amplifies when identity markers intersect.